2015
DOI: 10.1016/j.jped.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Practices related to late-onset sepsis in very low-birth weight preterm infants

Abstract: The knowledge of the practices of each center allowed for the identification of aspects to be improved as a strategy to reduce LOS, including: alcohol gel use, hand hygiene training, implementation of catheter teams, and wise use of antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…23 A multicenter study conducted by the RBPN between 2009 and 2010 showed 50% of late sepsis in premature infants <1500 g ranging from 29 to 72% between centers, with 27% accounting for confirmed late sepsis and 23%, clinical sepsis. 24 A RBPN cohort study on premature infants <1500 g, conducted between 2006 and 2008, also showed that late sepsis is common in premature infants <1500 g, with an incidence of 24% for sepsis confirmed with blood culture, and is associated with higher mortality. 25 A cohort study performed in Spain between 2006 and 2012 on newborns <30 weeks and/or <1500 g verified a 17.2% incidence of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…23 A multicenter study conducted by the RBPN between 2009 and 2010 showed 50% of late sepsis in premature infants <1500 g ranging from 29 to 72% between centers, with 27% accounting for confirmed late sepsis and 23%, clinical sepsis. 24 A RBPN cohort study on premature infants <1500 g, conducted between 2006 and 2008, also showed that late sepsis is common in premature infants <1500 g, with an incidence of 24% for sepsis confirmed with blood culture, and is associated with higher mortality. 25 A cohort study performed in Spain between 2006 and 2012 on newborns <30 weeks and/or <1500 g verified a 17.2% incidence of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is resistance to oxacillin in many neonatal units, the administration of this drug associated with amikacin was effective in saving the CVC in 13 cases of CRBSI. Brazilian studies prove the efficacy of anti-staphylococcal β lactam to treat CRBSIs (33,38) .…”
Section: Discussionmentioning
confidence: 99%
“…De modo geral, os três hospitais avaliaram de forma positiva a retirada de adornos, trazendo um percentual elevado da prática de diminuição do risco de infecção, do conhecimento dos protocolos e, consequentemente, de uma cirurgia mais segura [12].…”
Section: Discussionunclassified